A Clinical Study on Chronic Subdural Hematoma and its Surgical Management at a Tertiary Care Hospital in the Eastern Part of Nepal - Singh, Sunil; Kafle, Prakash; Joshi, Narendera Prashad; Kafle, Aakash; Karki, Tejendra (Journal of Nobel Medical College, 2025)
Background: Chronic subdural hematoma is a common neurosurgical condition, particularly in elderly patients, often associated with minor head trauma and requiring surgical intervention. This study aims to analyse the demographic patterns, clinical presentation, management, complications, and outcomes.Materials and Methods: A retrospective study was conducted on 51 patients who underwent surgical treatment for chronic subdural hematoma. Demographic details, clinical presentation, history of trauma, associated comorbidities, radiological findings, surgical techniques, intraoperative findings, complications, and outcomes were collected and analyzed.Results: In the present study, a total of 51 cases were analyzed for the study. There was male predominance (82.35%) in the study with male-to-female ratio of 5:1. The age of study population ranged from 25 to 88 years, with a median of 54 years (±16.52 SD). Headache was the most common symptom (51%). A history of head trauma within eight weeks was reported in 94.1% of cases. The most common comorbidities were diabetes mellitus (23%). Radiological assessment revealed right-sided hematomas in 56.9% of cases, with 41.2% exhibiting a midline shift greater than 10 mm. Single burr hole drainage was the most performed procedure (78.4%), followed by two burr hole drainage (13.7%), mini craniotomy (5.9%), and decompressive hemicraniectomy (2%). The overall complication rate was low, with recurrence occurring in 3.9% of cases. The functional outcomes were favourable, with 92.2% achieving good recovery at discharge.Conclusion: Chronic subdural hematoma predominantly affects elderly males and is strongly associated with prior head trauma. Burr hole drainage remains the preferred surgical technique.